From personal values to entrepreneurial intention: a systematic literature review. Issue 1 (16th October 2020) - Hueso, Juan Alberto; Jaén, Inmaculada; Liñán, Francisco
Abstract : Purpose: This systematic literature review (SLR) analyses the existing contributions, jointly studying personal values (PVs) and intentions in entrepreneurship. Despite the long tradition that these two constructs enjoy in social psychology, they have only recently been considered together in entrepreneurship research. Design/methodology/approach: To conduct this SLR, three widely used databases were searched (Scopus, ABI-INFORM and Web of Science). A total of 451 initial hits were successively narrowed down to a final list of 22 journal articles matching the inclusion criteria. This field of research is very recent since the selected papers have all been published since 2011, half of which have appeared since 2017. Findings: The predominant approach in these papers was the consideration of PVs as antecedents in the formation of entrepreneurial intentions (EIs). In particular, basic human values (BHV) theory for PVs and the theory of planned behaviour (TPB) for intentions are the prevalent frameworks. The influence of PVs differs notably depending on the motivational antecedent of intention being considered and also on the specific (general vs social) EI analysed. Originality/value: This SLR is, to the best of the authors' knowledge, the first review that addresses this fast-growing area of research. It provides a comprehensive mapping of the contributions to date as well as an integrative conceptual framework to synthetise accumulated knowledge. It also identifies subsisting knowledge gaps and a number of future research opportunities.